Efektifitas Kompres Hangat dan Kompres Dingin terhadap Tingkat Nyeri Balita Pasca Outbreak Response Immunization (ORI) - Reza Dwi Agustiningrum; Mira Triharini; Praba Diyan Rachmawati (Universitas Airlangga, 2019)
Introduction: The Medical treatment which carried out by using needles, such as immunization, is a source of pain for children. the importance of evidence-based immunization strategies is used to reduce pain. Pain management with compresses that can be done before immunization in the injection area is considered capable of reducing pain in children. Warm compresses can cause physiological effects, the effects of giving warm compresses can reduce the pain. Cold compresses proved to be an effective way to reduce pain during immunization because it increases endorphins and suppresses prostaglandins so that it can increase pain thresholds. The purpose of this study is to explain the effectiveness of using warm compresses and cold compresses to the pain level in toddlers after ORI diphtheria immunization.Methods: Analytical This study was pre-experimental with posttest only design. Data collection was carried out with FLACC scale sheets. The number of respondents as many as 66 toddlers was taken by inclusion and exclusion criteria with purposive sampling technique. Data were analyzed using Mann-Whitney analysis.Results: the average pain in compress warm group of 4.48 in the cold compress 2.91. However statistical test Mann-Whitney point a difference meaningful influence in both group on the pain of p = 0.001. Cold compress more effective to reduce the pain with the mean the difference between of 25.41 than warm compress of 41.59Conclusion: Increasing Cold compresses are more effective in reducing the level of pain in toddlers after ORI diphtheria immunization. Cold compresses with the temperature of 15° c that were conducted before the act of injection can be used as the management of pain non pharmacology to lower the level of pain in toddler after ORI diphtheria immunization.